1989
DOI: 10.1002/eji.1830190502
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of fetal PVG rats to induction of allograft tolerance

Abstract: Artificially induced immunological tolerance is often envisaged as experimental mimicry of events which occur naturally during the acquisition of self tolerance. Thus, it has been inferred that similar circumstances will facilitate the induction of both types of unresponsiveness. Since tolerance to most self determinants appears to have been established by the time of birth and allograft tolerance can be experimentally induced more readily, if not exclusively, in very young animals, it is commonly assumed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It could be argued, however, that the response induced by injecting the same dose of virus into a young versus an old mouse is not a valid comparison (21). In addition, a number of studies have shown that a graft given before the development of the immune system still leads to rejection of that tissue (22)(23)(24)(25)(26)(27)(28). This is even true for grafts mismatched for as little as one minor histocompatibility (minor-H) antigen (29), and argues strongly against a tolerance window early in life.…”
Section: The Modelsmentioning
confidence: 99%
“…It could be argued, however, that the response induced by injecting the same dose of virus into a young versus an old mouse is not a valid comparison (21). In addition, a number of studies have shown that a graft given before the development of the immune system still leads to rejection of that tissue (22)(23)(24)(25)(26)(27)(28). This is even true for grafts mismatched for as little as one minor histocompatibility (minor-H) antigen (29), and argues strongly against a tolerance window early in life.…”
Section: The Modelsmentioning
confidence: 99%
“…results], determinations after injection via intravenous and intraperitoneal routes were performed after 1, 6, and 96 h; the intraperitoneal route takes more than 6 and less than 96 h to 'stabilize' in fetuses. Furthermore, McCullagh [6] noticed that the success of tolerance induction in fetal rats depends on the infusion route and that the intraperitoneal route of cell administration in fetal rats was found to be less efficient than the intravenous route, even 2 weeks after injection. Immunological tolerance was induced in rat fetuses before 19 days [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, McCullagh [6] noticed that the success of tolerance induction in fetal rats depends on the infusion route and that the intraperitoneal route of cell administration in fetal rats was found to be less efficient than the intravenous route, even 2 weeks after injection. Immunological tolerance was induced in rat fetuses before 19 days [6,7]. Immunological maturation in the rat begins at 14-16 weeks of gestation [27] when the fetuses are developed enough to resist in utero injections.…”
Section: Discussionmentioning
confidence: 99%